O culto da performance na publicidade: subjetividade feminina em tempos velozes - Queiroz Neto, Valdemir Pereira de (2013)
The realization of this work was motivated by a concern about the new structuration forms of feminine subjectivity produced by the Culture Industry and Publicity, which are considered as a privileged symbolic instance of the contemporaneous consumer society. The object of study consists in the investigation of psychosocial meanings in publicities directed to the feminine public that privilege the enterprise culture and the cult of velocity through sports and hedonistic consumerism activities as models of identity prescription. To do so, some aspects that allowed the emergence of scientific activity and the instrumental rationality as “spokesperson” and carrier of modernity were discussed but also as the establisher of a knowledge form legitimated in the name of progress at any cost, and because of that, a powerful mean of domination. With the intention of showing the means through which contemporaneous publicity is capable of producing subjectivity that may result in ideological domination and reproduction of consumerist behavior, part of this study was dedicated to the discussion on publicity, its function, social meaning and strategic forms of submitting human desire to the market logic. Critical Theory from Frankfurt School was adopted as the theoretical-methodological axis besides contemporaneous authors as Birman, Costa, Lipovetsky , Lasch, Ehremberg, Kehl, Severiano, Aquino, Soares, among others The empirical research was developed from the collection of publicity ads directed to the feminine public in Women’s Health and Você SA magazines between 2011 and 2013. Publicity ads that express appeal to the professional success through the exercise of multiple roles, to the sport as facilitator of high-level performances and to the consumerism as expression of happiness were selected .These themes constituted the categories of analysis: the discourse of happiness, enterprise and sport. A qualitative analysis of theoretical-critical nature was chosen as methodological strategy of the cited discourses enabling reflection on the merchandising of human attributes.